Arranjos produtivos locais, capital social organizacional e desenvolvimento local : um estudo de caso no APL Coureiro-Calçadista de Campina Grande-PB - Andrade, Elisabeth de Oliveira (2011)
Local Productive Arrangements (LPAs) are emerging as a new organizational format that induce the strengthening of enterprises, especially those of small and medium businesses, through coordinated action between the different links that comprise it (business actors, institutions and the government itself) involving subjective aspects such as trust, cooperation, partnerships, collective strategies, among others. In this sense, social capital is presented as a preponderant tool in this process by fostering the sharing of norms and values among the actors participating in an arrangement as well as increase the capacity of synergy, participation and innovation. It is worth noting that the consolidation of an LPA is the result of a strong relationship between companies, institutions, public and private organizations and civil society, where the establishment of ongoing relationships between these actors leads to the spread of capital and especially in promoting local development, from the generation of employment and income, economic growth and inclusive social development policies. Based on these considerations, this study aims to examine the contribution level of the LPA of Leather and Footwear in Campina Grande - PB for local development, according to the organizational social capital model proposed by Román and Rodriguez (2004). The model titled Dimensions of social capital, Mechanisms and Results, encompasses a range of issues and indicators for targeted analysis of social capital within organizations, making a direct link with the local development process. In parallel, there is the incorporation of the methodology proposed by Olivares and Dalcol (2010), which allows to calculate the contribution level of production clusters for local development. Regarding methodological procedures, this study is characterized as exploratory and descriptive, conducted in the form of case study. The results allowed to find a final contribution degree of LPA of Leather and Footwear for the development of Campina Grande - PB of 0.51. Although it falls into an acceptable level, it is prudent to incorporate effective steps for strengthening and engagement between business and institutional agents, promoting the intensification of collective behavior and synergistic, in order to minimize and/or extinguish the diagnosed bottlenecks by converting them in greater ease of the arrangement and therefore of the city in which it is inserted.